2022
DOI: 10.3389/fimmu.2022.923477
|View full text |Cite
|
Sign up to set email alerts
|

Effects of helicobacter pylori on tumor microenvironment and immunotherapy responses

Abstract: Helicobacter pylori is closely associated with gastric cancer. During persistent infection, Helicobacter pylori can form a microenvironment in gastric mucosa which facilitates the survival and colony formation of Helicobacter pylori. Tumor stromal cells are involved in this process, including tumor-associated macrophages, mesenchymal stem cells, cancer-associated fibroblasts, and myeloid-derived suppressor cells, and so on. The immune checkpoints are also regulated by Helicobacter pylori infection. Helicobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 182 publications
1
22
0
Order By: Relevance
“…In short, the influence of PPIs on the immune system remains unclear. We propose that PPIs may cause immune system dysfunction through their own function or through changes in the gut microbiota 97,98. Further exploration is needed to clarify the mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, the influence of PPIs on the immune system remains unclear. We propose that PPIs may cause immune system dysfunction through their own function or through changes in the gut microbiota 97,98. Further exploration is needed to clarify the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that PPIs may cause immune system dysfunction through their own function or through changes in the gut microbiota. 97,98 Further exploration is needed to clarify the mechanism. For ORR and irAEs, the pooled analysis demonstrated that PPI use did not affect ORR or irAEs in advanced cancer patients treated with ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…Beside significantly reducing tumour mass, and cell migration, another promising effect of curcumin could also be that it could target tumour microflora. It is well known that Helicobacter pylori is strongly associated with the induction and development of gastric tumours, which includes metastatic activity [291,292]. It was reported that curcumin displayed potent activity against various strains of Helicobacter pylori (MIC ~ 5-50 μg/mL) [293,294].…”
Section: Future Directionmentioning
confidence: 99%
“…and Epstein-Barr virus (EBV) are the main infection-related factor (92)(93)(94). H. pylori can inhibit the CD8 + CTLs by myeloid-derived suppressor cells (MDSCs) and induce the up-regulated expression of PD-L1 of tumor epithelial cells and macrophages, thereby inducing the resistance of gastric cancer to ICB therapy against PD-1/PD-L1 (95,96). Xu et al have shown that the induction of Trm proliferation and differentiation can enhance the local immune response to H. pylori (97).…”
Section: Tissue-resident Memory T Cells In Gastric Cancermentioning
confidence: 99%